Tersembunyi tapi Nyata: Makna Pertolongan Allah dari Balik Layar dalam Kitab Ester - Nendissa, Julio Eleazer; Manoppo, Febri Kurnia; Mongkau, Dedy Efendy (Sekolah Tinggi Teologi Parakletos Tomohon, 2024)
Abstract: The theological meaning in the book of Esther is very difficult for lay people to understand because the name and power of God are not visible, so this is the characteristic and character of the book of Esther. The controversy over the book of Esther is when it maintains its spiritual existence so that it is tested whether the book of Esther is a holy book or not with various considerations regarding the controversy over the word of God. The purpose of this article is to explain and analyze the meaning of God's help based on God's absence throughout the storyline in the book of Esther so that God's invisible existence can be interpreted theologically. This article uses qualitative research with a library study approach, namely books and journals as references for researching existing problems. This article offers new understanding through the findings obtained, namely the theology of the book of Esther as a depiction of a woman able to provide resistance and appear confident and responsible because she was chosen by the king. Another finding, although the book of Esther does not contain the word God, God's help is also not visible or hidden, it can be felt by the figure of Esther in a real way through the incident of Esther being chosen by the king as queen, God's help through Esther which turned the situation around for the Jews. Abstrak: Makna teologis dalam kitab Ester sangat sulit dicerna sebagai kaum awam karena nama dan kuasa Allah tidak tampak secara jelas sehingga ini menjadi ciri serta karakter dari kitab Ester. Kontroversi kitab Ester ini ketika mempertahankan eksistensi kerohanian sehingga diuji kelayakan bahwa kitab Ester sejatinya kitab suci atau bukan dengan berbagai pertimbangan terhadap kontroversi kata Allah. Tujuan dari tulisan ini ialah menjelaskan dan menganalisis makna pertolongan Allah dengan berlandaskan pada ketidakhadiran Allah di kitab Ester yang secara sengaja tidak menceritakan sosok Allah dengan penuh kebaikan dan pertolongan untuk muncul dalam kitab tersebut sehingga keberadaan Allah yang tidak tampak itu bisa dimaknai secara teologis. Artikel ini memakai penelitian kualitatif dengan pendekatan studi pustaka yakni buku dan jurnal sebagai acuan untuk dipakai meneliti persoalan yang ada. Artikel ini menawarkan pemahaman baru lewat temuan yang didapatkan yaitu teologi kitab Ester sebagai gambaran sosok wanita mampu memberikan perlawanan dan tampil percaya diri serta bertanggungjawab karena dipilih oleh raja. Temuan lainnya, walaupun kitab Ester tidak mengandung kata Allah dan pertolongan Allah juga tidak tampak kasat mata atau tersembunyi itu bisa dirasakan oleh sosok Ester secara nyata melalui peristiwa Ester dipilih oleh raja sebagai ratu, pertolongan Allah melalui Ester yang membalikkan keadaan Yahudi.